Hybrid Low Bitrate Audio Coding Using Adaptive Gain Shape Vector Quantization - Mehrotra, Sanjeev; Chen, Wei-ge; Koishida, Kazuhito; Thumpudi, Naveen (Proceedings Workshop on Multimedia Signal Processing, 2008)
Audio coding at low bitrates typically suffers from artifacts caused by bandwidth truncation. In this paper we present a novel scheme to code audio signals at low bitrates which uses a traditional scalar quantization followed by entropy coding to code some portions of the spectrum (typically the lower portion). The other portions (typically the higher portions) of the spectrum are coded at a low bitrate using an adaptive gain shape vector quantizer where the codebook for vector quantization is formed by unmodiﬁed or modiﬁed versions of the portions of the spectrum which have already been coded. Fixed pretrained codebooks are also available for use in certain cases. The use of such a scheme results in an audio codec which has been shown to be among the best audio codecs available at low bitrates. In addition, the decoder complexity of this audio codec is signiﬁcantly lower than any other codec of equal quality at low bitrates.